Allison Glazebrook and Barbara Tsakirgis (eds) Houses of ill repute: the archaeology of brothels, houses, and taverns in the Greek world - Meens, Anna (Journal of Greek Archaeology, 2016)
Recently archaeological scholarship on ancient Greece has widened its scope from monumental public buildings and town planning to include the sphere of houses, households and everyday life. The present volume, Houses of ill repute: The archaeology of brothels, houses, and taverns in the Greek world, edited by Allison Glazebrook and Barbara Tsakirgis, presents a welcome nuance by considering the realm between the public and the private in the Greek world. Written sources suggest we need to envision diverse urban landscapes in which housing and commercial areas are intertwined, and in this book a variety of contributors explore the possibilities for distinguishing such a reality with (work)shops, houses, brothels and taverns archaeologically in different urban contexts.